Efficient Energy and Electrostatic Properties Calculations at the MP2 Theory Level: A Case Study of Density Matrix-Based Computational Quantum Chemistry - Mazur, Grzegorz; Makowski, Marcin; Sumera, Jakub; Kowalczyk, Krzysztof (Computing and Informatics, 2012)
Wavefunction-less, density matrix-based approach to computational quantum chemistry is briefly discussed. Implementation of second-order M oller-Plesset Perturbation Method energy and dipole moment calculations within the new paradigm is presented. Efficiency and reliability of the method is analyzed.